Effects of school-based high-intensity interval training on body composition, cardiorespiratory fitness and cardiometabolic markers in adolescent boys with obesity: a randomized controlled trial - Cao Meng; Tang Yucheng; Li Shu; Zou Yu (BMC, 2022)
Abstract Background With accumulating evidence suggesting that CVD has its origins in childhood obesity. The purpose of this study was to determine the effect of a real-world school-based high-intensity interval training intervention on body composition, cardiorespiratory fitness and cardiometabolic markers in obese boys aged 10 to 13 years. Methods Forty-five adolescent boys with obesity (age = 11.2 ± 0.7 years, BMI = 24.2 ± 1.0 kg/m2), were randomized to high-intensity interval training group (HIIT, n = 15), moderate-intensity continuous training group (MICT, n = 15), or a control group (CON, n = 15). The intervention groups performed three weekly exercise sessions over 12 weeks. HIIT group performed two sets of eight bouts of 15 s run at high-intensity [90 ~ 100% maximal aerobic speed (MAS)] separated by eight bouts of 15 s recovery run at low-intensity (50% MAS), MICT group performed 30 min run at moderate intensity (60 ~ 70% MAS) and CON group were instructed to continue their normal behaviors. All participants had indices of body composition, cardiorespiratory fitness (CRF) and cardiometabolic markers measured at baseline and post-intervention. Statistical differences between and within groups were determined by use of two-way analysis of variance (ANOVA) with repeated measures. Results Following the school-based training program, BMI and body fat mass decreased (BMI: − 1.8 kg/m2 vs. - 1.2 kg/m2, P < 0.01; FM: − 1.6 kg, P < 0.05 vs. -3.7 kg, P < 0.01) in HIIT and MICT group, but there was no significant difference between the two interventions; $$\dot{V}{O}_{2peak}$$ V ˙ O 2 peak both increased significantly in two intervention groups, and the increment of HIIT group was significantly greater than that of MICT (6.1 mL/kg/min vs. 3.8 mL/kg/min, P < 0.01), Visceral adipose tissue was significant decrease in HIIT group (− 53 g vs. -17 g, P < 0.01) whilst the MICT group experienced a significant decrease in body fat percentage (− 3.1 ± 1.0 kg, P < 0.01), but there were no significant difference between the two interventions. Low-density lipoprotein cholesterol decreased only in HIIT group (− 17.2%, P < 0.05). Significant decrease in the usual index of insulin resistance (HOMA-IR) occurred in HIIT and MICT groups (− 27.3 and − 28.6%, respectively; P < 0.05). Conclusions Our results demonstrated that high-intensity interval training based on running can be used to improve the physical health of obese adolescents in school. Further investigations involving a larger cohort of participants, taken from different schools, is recommended. Trial registration title Effect of High Intensity Interval Training on Obese Children and Adolescents, time 16/12/2017, ID ChiCTR-IOR-17013992 , website http://www.chictr.org.cn